Copper(II)-Catalyzed Selective CAr-H Bond Formylation: Synthesis of Dialdehyde Aniline - Guo, Shiwei; Li, Yinghua; Fan, Weibin; Liu, Zhiqi; Huang, Deguang (Frontiers in Chemistry, 2022)
A simple and efficient method for the synthesis of dialdehyde aniline in good yields (up to 83%) is explored using Cu(OTf)2 as the catalyst, Selectfluor as the radical initiator, and DMSO as both the carbon and oxygen sources. Experimental studies indicate that the reaction is achieved by the formylation of two CAr-H bonds, first at the para-position and then at the ortho-position. A possible mechanism is proposed, including the thermal homolysis of Selectfluor, the Cu(II)-facilitated formylation of the CAr-H bonds, and the hydrolysis of the amide under alkaline conditions in air atmosphere.